BER-Optimized Robust Precoder Design for MIMO-OFDM Systems with Insufficient CP - Akhtar, Javed; Bedi, Amrit S.; Rajawat, Ketan; Jagannatham, Aditya K. (2016 IEEE Global Communications Conference (GLOBECOM), 2016)
This paper considers a robust precoder design for MIMO-OFDM systems with insufficient cyclic prefix (CP). Interference alignment is utilized to formulate the precoder design problem as a bit error rate (BER) minimization problem subject to a total power constraint. To this end, the precoder is designed to be robust to the errors in the available channel estimates, by considering the worst-case BER for optimization. Interestingly, channel estimates at both transmitter and receiver are allowed to be in error. Extensive simulations are carried out to compare the performance of various MIMO-OFDM systems with and without robust precoders.